INTERVENSI CONTRACT RELAX HAMSTRING DAN HOLD RELAX QUADRICEPS LEBIH BAIK DIBANDING CONTRACT RELAX HAMSTRING DAN ISOTONIC EXERCISE QUADRICEPS DALAM MENINGKATKAN FLEKSIBILITAS HAMSTRING PADA IBU-IBU PKK DI BANJAR JAMBE BELODAN, DESA DAUH PEKEN, TABANAN - Putu Santi Krishna Megasari; Ni Luh Nopi Andayani; Susy Purnawati; Ida Ayu Dewi Wiryanthini (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2018)
ABSTRACT Lack of physical activity to excessive physical activity, pregnancy and lack of exercise in women affects the hamstring muscle shortening if left unchecked will cause a loss of flexibility in the muscles. This study is an experimentalresearch design with Two Group Pre and Post Test Design involving 22 samples were divided into 2 groups: treatmentgroup 1 with intervention Contract relax hamstring and hold relax quadriceps and treatment group 2 with interventionContract relax hamstring and Isotonic exercise quadriceps , Paired samples t-test showed the value of p = 0.000 in bothgroups. 22.82 (SB 7.85) cm in group 1 and 16.54 (SB 6.43) cm in group 2. The test results independent sample t-testshowed the value of p = 0.000 on the difference increased flexibility of the hamstring muscles. The conclusion of thisstudy is the contract hold-relax relax the hamstring and quadriceps better than contract relax the hamstring andquadriceps Isotonic exercise in improving the flexibility of the hamstring on Women of PKK in Banjar Jambe Belodan,Desa Dauh Peken, Tabanan. Keywords: hamstring tightness, flexibility of hamstring muscles, stretching, contract relax, hold relax, Isotonicexercise